7-6x>=1/3(9x-1)
7-6x3x-1/3
-6x-3x
9x
x:9
x
7-6X>=3x-1/37 1/3>=9x
22/3>=9x
x<=22/27
x принадлежит (-бесконечности;22.27квадратная скобка
7-6x>=1/3(9x-1)
7-6x
3x-1/3
-6x-3x![\geq](/tpl/images/0103/6749/d872a.png)
![-7\frac{1}{3}](/tpl/images/0103/6749/7104e.png)
9x![\leq](/tpl/images/0103/6749/46cd6.png)
![7\frac{1}{3}](/tpl/images/0103/6749/8bc7d.png)
x![\leq](/tpl/images/0103/6749/46cd6.png)
:9
x![\leq](/tpl/images/0103/6749/46cd6.png)
![\frac{22}{27}](/tpl/images/0103/6749/28f9a.png)
7-6X>=3x-1/3
7 1/3>=9x
22/3>=9x
x<=22/27
x принадлежит (-бесконечности;22.27квадратная скобка